The Role of the Learner’s Native Culture in EFL Dictionaries: An Experimental Study - Pujol, Dídac; Corrius, Montse (Lexikos, 2013)
This article aims to demonstrate the hypothesis that the use of native culture (C1) in EFL learners’ dictionary definitions and/or examples is useful in the comprehension of the looked-up words. This is done by means of a survey involving more than 100 lower-intermediate EFL Catalan students. The subjects were first presented with a pre-test in which they had to translate 30 English words. Then they were divided into two groups, each of whom had to take a different test. Test 1 contained the definitions of the 30 words taken from a dictionary aimed at a global audience, whereas in test 2 the definitions were taken from a culturally nativized dictionary, that is, a dictionary that included C1 elements. In the tests, the students were asked to translate again the 30 English headwords given in the pre-test. After comparing the results of the pre-test with those of the tests, the study concludes that students who use an EFL dictionary that includes C1 references have more than double the possibilities of understanding the meaning of a new looked-up word than those who do not. The results obtained confirm for the first time in the field of pedagogical lexicography the tenets of schema theory, which highlights the importance of background (e.g. cultural) knowledge to improve reading comprehension. The main implication of this finding for lexicography is that it is desirable that designers of EFL dictionaries deploy nativized versions, especially at lower levels, in order to facilitate comprehension of the foreign language.